Dante Gabriel Rossetti's Pre-Raphaelites Beginnings: “Mary’s Girlhood” e The Girlhood of Mary Virgin - Chiara Moriconi (Between, 2012)
Right from the beginnings of Dante Gabriel Rossetti’s career, his most striking quality lies in his deep commitment to a continual interrelation between the arts of poetry and of painting. This essay aims at revealing the strategies applied to the intersemiotic process taking place between Rossetti’s first Pre-raphaelite canvas, The Girlhood of Mary Virgin, and the two sonnets written to ‘illustrate’ it. To better examine the shift between different media and Rossetti’s own appraisal of such a translating process, reference has been made to some of the great names of the contemporary debate about intersemiotic translation, such as Greimas, Eco and Jakobson. By applying such modern tools of intersemiotic analysis to the artist’s first double work of art it will eventually be clear how Rossetti’s Pre-raphaelite phase is anything but an immature debut in the Victorian artistic scene. Many of the features of his early career are in fact to be found as faithfully maintained in the more complex development of his maturer art. This essay will show how The Girlhood of Mary Virgin and “Mary’s Girlhood” are to be considered as a true manifesto of Rossetti’s entire career and of his appraisal of the relation between the sister arts.